Talempong Kayu dalam Kehidupan Sosial Nagari Kayu Gadang - Suci Rahma Elfita; Nadia Fulzy; Andar Indra Sastra (INDO PUBLISHING, 2026)
This study discusses Talempong Kayu in the social life of the people of Nagari Kayu Gadang. Talempong Kayu is a traditional art form that has grown and developed within the community as part of a cultural heritage possessing social, cultural, and aesthetic values. Its existence not only serves as a means of entertainment but also plays an important role in various social activities, such as traditional ceremonies, religious celebrations, welcoming events for guests, and other community activities. This study aims to describe the form of presentation of Talempong Kayu and analyze its role in the social life of the people of Nagari Kayu Gadang. This research employs a qualitative method with a descriptive approach. Data were collected through observation, interviews with community leaders, artists, and Talempong Kayu performers, as well as documentation related to the research object. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that Talempong Kayu has a strong social function in the lives of the people of Nagari Kayu Gadang. This art form serves as a medium of social communication, strengthens relationships among community members, and functions as a means of preserving local cultural values passed down from generation to generation. Furthermore, Talempong Kayu plays a role in building the cultural identity of the community and reinforcing a sense of togetherness in various social activities. Its continued existence today demonstrates the community’s awareness and commitment to preserving traditional arts as an essential part of their regional cultural identity